Application of Kahoot Interactive Quiz Learning Media to Increase Interest in Learning History of Class XI Comet Students at SMA Negeri 2 Medan - Arisna, Fitri; Sumantri, Pulung; Aisyah, Sitti (Jurnal Akuntansi Hukum dan Edukasi, 2024)
The aim of this research is to see the effectiveness of implementing Kahoot-based interactive quiz learning media in increasing interest in learning history in class XI Komet students at SMA Negeri 2 Medan. The method used in this research is classroom action research (PTK) methodology which consists of II stages (Cycles) using a quantitative approach. Questionnaires and observations are data collection instruments (techniques) that are used to see the level of students' interest in learning after using the Kahoot quiz learning media. The population taken was students from SMA Negeri 2 Medan with a sample of class XI Komet students consisting of 36 students consisting of 10 male students and 26 female students. Based on the results of the research that has been carried out, it is known that the results of the analysis of observation and questionnaire data in stage I which was carried out on 09 August 2024 obtained a percentage of 72.69% and in stage II which was carried out on 12 August 2024 it increased by 89.40%.  Based on the conclusions that have been produced, the researcher states that the use of Kahoot-based interactive quiz learning media has been proven to stimulate and foster students' interest in learning.